Rational mpox vaccine design: immunogenicity and protective effect of individual and multicomponent proteins in mice - Xueting Cheng; Yawei Wang; Baoying Huang; Jialuo Bing; Tangqi Wang; Ruiwen Han; Shuting Huo; Shucai Sun; Li Zhao; Chang Shu; Yao Deng; Wenjie Tan (Emerging Microbes and Infections)
The 2022 global mpox virus (MPXV) outbreak highlights the urgent need for safer, next-generation vaccines. We compared the immunogenicity and protective efficacy of individual and multicomponent membrane proteins of MPXV virions in mice to inform the development of a recombinant subunit vaccine against mpox. BALB/c mice were immunized with eukaryotically expressed A35R, A29L, B6R, and M1R proteins, administered individually or in multicomponent combinations with an Al(OH)3 + CpG oligodeoxynucleotide adjuvant. Three multicomponent protein vaccines (A29/B6, A29/B6/M1, and A29/B6/M1/A35) provided complete protection, but others (individual protein and A35/M1 combinations) provided partial protection against challenge with high-lethal doses of vaccinia virus Western Reserve (VACV-WR). Additionally, A29/B6 conferred partial protection, whereas A29/B6/M1 and A29/B6/M1/A35 provided complete protection against ectromelia virus (ECTV), with A29/B6/M1 being most effective. All vaccines induced strong antigen-specific immunoglobulin G (IgG) and cellular immunity, whereas only four (M1, A35/M1, A29/B6/M1, A29/B6/M1/A35) exhibited significant neutralizing activity against MPXV, VACV-Tiantan, and ECTV. Correlation analysis suggested that neutralizing antibodies and A35-/A29-/B6-specific cellular immunity act as complementary defense mechanisms, potentially providing first- and second-line protection against MPXV and related orthopoxviruses. Collectively, A29/B6/M1 demonstrated the best protective efficacy. This study provides novel insights into immunogen optimization and potential mechanisms for the development of vaccines against MPXV and other orthopoxviruses.